Solanaceae glycoalkaloids: α-solanine and α-chaconine modify the cardioinhibitory activity of verapamil. (31st December 2022) - Chowański, Szymon; Winkiel, Magdalena; Szymczak-Cendlak, Monika; Marciniak, Paweł; Mańczak, Dominika; Walkowiak-Nowicka, Karolina; Spochacz, Marta; Bufo, Sabino A.; Scrano, Laura; Adamski, Zbigniew
Abstract: Context: Solanaceae glycoalkaloids (SGAs) possess cardiomodulatory activity. Objective: This study investigated the potential interaction between verapamil and glycoalkaloids. Material and methods: The cardioactivity of verapamil and glycoalkaloids (α-solanine and α-chaconine) was tested in adult beetle ( Tenebrio molitor ) myocardium in vitro using microdensitometric methods. The myocardium was treated with pure substances and mixtures of verapamil and glycoalkaloids for 9 min with saline as a control. Two experimental variants were used: simultaneous application of verapamil and glycoalkaloids or preincubation of the myocardium with one of the compounds followed by perfusion with a verapamil solution. We used 9 × 10 −6–5 × 10 −5 M and 10 −9 –10 −5 M concentration for verapamil and glycoalkaloids, respectively. Results: Verapamil, α-solanine and α-chaconine showed cardioinhibitory activity with IC50 values equal to 1.69 × 10 −5, 1.88 × 10 −7 and 7.48 × 10 −7 M, respectively. When the glycoalkaloids were applied simultaneously with verapamil, an antagonistic effect was observed with a decrease in the maximal inhibitory effect and prolongation of t50 and the recovery time characteristic of verapamil. We also confirmed the expression of two transcript forms of the gene that encodes the α1 subunit of L-type calcium channels in the myocardium and brain with equal transcription levels of both forms in the myocardium and significant domination of the shorter form in the brain of the insect species tested. Discussion and conclusions: The results show that attention to the composition of the daily diet during therapy with various drugs is particularly important. In subsequent studies, the nature of interaction between verapamil and SGAs on the molecular level should be checked, and whether this interaction decreases the efficiency of cardiovascular therapy with verapamil in humans.